RESPON BEBERAPA VARIETAS DAN DOSIS BAHAN ORGANIK TERHADAP PERTUMBUHAN DAN HASIL MENTIMUN (Cucumis sativus L.) PADA TANAH ULTISOL - Iwandikasyah Putra; Irvan Subandar; Samsuar Samsuar (Universitas Teuku Umar, 2018)
This research to know response organic materials and some varieties to cucumber to result and growth atultisol and whet herthere is interaction both of factor.This research have been executed by in Garden Agriculture Faculity of TeukuUmar University Meulaboh, Aceh Barat Started 3 July up to 7 September 2015.This research to used is a randomized blokc desigh (RBD) with 3 x 4 and 3 with there replications. The first factor is varieties 3 level: Hercules, Mercy, and Wuku. The second factor is organic material; 4 level that is control (without treatmant),10 tons/hectare, 20 tons/hectare, and 30 tons / hectare set organic. The results showed that the varieties signifcantly affectted plant height 15, 20, and 25 days after plantiny length diameter fruit. Where as 15 and 20 days after planting, fruit weight and production tons/hectare. Showed no significant effect on dose organic plant heigh 15, 20, and 25 days after planting, fruit weigh, fruit length, fruit to diameter, and productions total tons/hectare. There was no significant interaction between varieties and organic material on all parameters of observation. Keywords: cucumber, organic materials, ultisol, varieties